Memorials Matter : Emotion, Environment and Public Memory at American Historical Sites - Ladino, Jennifer K. (Book collections on Project MUSE., 2019)
"Memorials Matter investigates how sites of memory in the American West influence emotions about historical conflict and national identity. The book compares seven diverse National Park Service sites to show how the natural landscapes and built structures combine with written texts at each site to generate emotion in individual tourists and shape our collective memory of traumatic events"--Provided by publisher.